'Planning ahead' among community‐dwelling older people from culturally and linguistically diverse background: a cross‐sectional survey. Issue 1 (12th July 2014) - Jeong, Sarah; Ohr, Seok; Pich, Jacqueline; Saul, Peter; Ho, Alan
<x xml:space="preserve">Abstract</x> Aims and objectives To explore preparedness of end‐of‐life care planning among community‐dwelling older persons of culturally and linguistically diverse background. Background To improve end‐of‐life care through advance care planning, the key concept 'Planning ahead' has been promoted in Australia. However, since the introduction of the model in 2008, it is not known whether 'Planning Ahead' practice by older people from culturally and linguistically diverse backgrounds has improved. Design A cross‐sectional survey. Methods A total of 453 community older adults (65+) who attended 17 day care centres in a region were invited to participate in the study. A total of 229 people completed the survey with a response rate of 50·5%. The questions relevant to this study include: (1) awareness of enduring guardian, advance care directive and advance care planning, (2) the preference for substitute decision‐makers and (3) the challenges experienced with advance care planning. Results Awareness of advance care planning was low, and completion of advance care directive was very low. 37·5% of Anglo Celtic group had an enduring guardian, compared with 15·5, 24·1 and 13·3% from Mediterranean, Eastern European and Asia/Pacific group, respectively. Children were the most preferred substitute decision‐makers more for Asia/Pacific group than Anglo Celtic, Mediterranean and Eastern Europeans. The various difficulties experienced included being time‐consuming, difficult to understand terms and forms, and do not know how to do it. Conclusion Regardless of cultural and ethnic backgrounds, a low level of 'Planning ahead' practices was apparent because of a lack of understanding of the concept, the forms and the processes involved. The gap identified between the existing legal/ethical frameworks and the preferences of older people as substitute decision‐makers adds new knowledge for further discussion. Relevance to clinical practice Nursing professionals are provided with an opportunity to improve their practice to meet the needs of older persons and their families in planning ahead for future treatment options.